Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To solve the equation [tex]\(-5x(7x - 4)(3x + 1)^2 = 0\)[/tex], we need to factorize and solve for [tex]\(x\)[/tex]. Let's break it down step-by-step.
### Step 1: Understand the Equation
The equation is [tex]\(-5x(7x - 4)(3x + 1)^2 = 0\)[/tex]. This equation is a product of three factors: [tex]\(-5x\)[/tex], [tex]\((7x - 4)\)[/tex], and [tex]\((3x + 1)^2\)[/tex].
### Step 2: Apply the Zero Product Property
According to the Zero Product Property, if a product of several factors is zero, then at least one of the factors must be zero. Thus, we can set each factor to zero and solve for [tex]\(x\)[/tex].
1. [tex]\(-5x = 0\)[/tex]
2. [tex]\(7x - 4 = 0\)[/tex]
3. [tex]\((3x + 1)^2 = 0\)[/tex]
### Step 3: Solve Each Factor Individually
#### Factor 1: [tex]\(-5x = 0\)[/tex]
To solve for [tex]\(x\)[/tex], we divide both sides by [tex]\(-5\)[/tex]:
[tex]\[ x = 0 \][/tex]
#### Factor 2: [tex]\(7x - 4 = 0\)[/tex]
To solve for [tex]\(x\)[/tex], we isolate [tex]\(x\)[/tex]:
[tex]\[ 7x - 4 = 0 \\ 7x = 4 \\ x = \frac{4}{7} \][/tex]
#### Factor 3: [tex]\((3x + 1)^2 = 0\)[/tex]
Since [tex]\((3x + 1)^2\)[/tex] is a square term, it is zero when the term inside the square is zero:
[tex]\[ 3x + 1 = 0 \\ 3x = -1 \\ x = -\frac{1}{3} \][/tex]
### Step 4: Compile the Solutions
The solutions to the equation [tex]\(-5x(7x - 4)(3x + 1)^2 = 0\)[/tex] are:
[tex]\[ x = 0, \quad x = \frac{4}{7}, \quad x = -\frac{1}{3} \][/tex]
### Conclusion
The values of [tex]\(x\)[/tex] that satisfy the equation [tex]\(-5x(7x - 4)(3x + 1)^2 = 0\)[/tex] are:
[tex]\[ x = 0, \quad x = \frac{4}{7}, \quad x = -\frac{1}{3} \][/tex]
These are the points where the given equation equals zero.
### Step 1: Understand the Equation
The equation is [tex]\(-5x(7x - 4)(3x + 1)^2 = 0\)[/tex]. This equation is a product of three factors: [tex]\(-5x\)[/tex], [tex]\((7x - 4)\)[/tex], and [tex]\((3x + 1)^2\)[/tex].
### Step 2: Apply the Zero Product Property
According to the Zero Product Property, if a product of several factors is zero, then at least one of the factors must be zero. Thus, we can set each factor to zero and solve for [tex]\(x\)[/tex].
1. [tex]\(-5x = 0\)[/tex]
2. [tex]\(7x - 4 = 0\)[/tex]
3. [tex]\((3x + 1)^2 = 0\)[/tex]
### Step 3: Solve Each Factor Individually
#### Factor 1: [tex]\(-5x = 0\)[/tex]
To solve for [tex]\(x\)[/tex], we divide both sides by [tex]\(-5\)[/tex]:
[tex]\[ x = 0 \][/tex]
#### Factor 2: [tex]\(7x - 4 = 0\)[/tex]
To solve for [tex]\(x\)[/tex], we isolate [tex]\(x\)[/tex]:
[tex]\[ 7x - 4 = 0 \\ 7x = 4 \\ x = \frac{4}{7} \][/tex]
#### Factor 3: [tex]\((3x + 1)^2 = 0\)[/tex]
Since [tex]\((3x + 1)^2\)[/tex] is a square term, it is zero when the term inside the square is zero:
[tex]\[ 3x + 1 = 0 \\ 3x = -1 \\ x = -\frac{1}{3} \][/tex]
### Step 4: Compile the Solutions
The solutions to the equation [tex]\(-5x(7x - 4)(3x + 1)^2 = 0\)[/tex] are:
[tex]\[ x = 0, \quad x = \frac{4}{7}, \quad x = -\frac{1}{3} \][/tex]
### Conclusion
The values of [tex]\(x\)[/tex] that satisfy the equation [tex]\(-5x(7x - 4)(3x + 1)^2 = 0\)[/tex] are:
[tex]\[ x = 0, \quad x = \frac{4}{7}, \quad x = -\frac{1}{3} \][/tex]
These are the points where the given equation equals zero.
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.